Tungsten gallium-phosphate glasses for high energy radiation detection - Lodi, Thiago Augusto (2022)
Scintillators are materials that convert a single photon of high-energy ionizing radiation, like X-rays, γ-rays, neutrons, α and β particles, into UV-visible photons. Scintillation detectors, which usually consist of a scintillator and photodetector, have played an important role in radiation detection applications, such as in industrial and medical imaging, homeland security and high energy physics experiments. In order to be used as a scintillator, a material must contain luminescent centers which are either extrinsic, when doped with active ions such as the trivalent rare-earth ions, or intrinsic, when the emission originates from molecular centers or lattice defects. Typically, scintillators are inorganic single-crystals due to their high density and excellent emission efficiency. However, the synthesis of these materials, in limited sizes and shapes is extremely costly and time-consuming, hindering industrial production in large market scale. Alternatively, lower-cost materials which offer larger possibilities of shaping, such as glasses, have been investigated this application. Glass is an extremely versatile material that in general provides cost-effective, large-scale production, being easily processed into complex geometries, including special optical fibers. This doctorate project was focused on the development of glasses in the compositional system NaPO3-Ga2O3-Na2WO4 and their detailed characterization from the thermal, structural, spectroscopic and optical viewpoints, in view of their promising application as scintillators. The glasses were obtained with excellent optical quality, very good chemical and thermal stability, and they were characterized by Differential Scanning Calorimetry (DSC), volumetric density measurements, X-ray diffraction, Raman spectroscopy, Nuclear Magnetic Resonance (NMR), Fourier Transform Infrared (FT-IR), X-ray photoelectron spectroscopy (XPS), UV-vis absorption, photoluminescence (emission and excitation) and radioluminescence. The robustness of the materials associated to its optimum spectroscopic, optical and radioluminescent response indicate that they are promising materials for scintillating devices, worth of further investigation and developments.